Eksplorasi Etnomatematika yang Terdapat dalam Corak Lipa’ Sa’be Mandar sebagai Sumber Belajar - Kiky Nakesya A.S; Rusnah; Adi Sulaiman M.Siddiq; Andi Dian Angriani; Tampa, Alimuddin (Alauddin Journal of Mathematics Education, 2024)
This study aims to explore the relationship between mathematics and culture contained in the Lipa' Sa'be Mandar style as a student learning resource. The type of research used is qualitative research with an ethnographic approach. The subject of this research is Mandar people coinciding in Suruang Village, Campalagian District, Polewali Mandar Regency. The instrument used is the researcher himself and also supporting instruments such as interview guides but the possibility of interview questions developing according to the needs of the researcher. Data collection techniques consist of observation, interviews and documentation. Based on the research results obtained that part of the pattern on Lipa' Sa'be Mandar is essentially related to the geometric shapes of flat shapes, especially in the motif called sure' and also part of the flower motif that displays elements of flat geometry. The patterns of Lipa' Sa'be in which there is a mathematical concept of flat geometry are the patterns of Lipa’ Sa’be Sure’ Padhadha, Sure’ Mara’ Dia, Sure’ Padada Saripa, Sure’ Bunga, serta Sure’ Batu Dadzima with a square shape while there are some variants of Mandar Lipa' Sa'be in which there are patterns with rectangular shapes, circular, triangles, and rhombuses.